UNDERSTANDING WOMEN'S ENTREPRENEURIAL JOURNEY: DETERMINANTS OF LABOR MARKET PARTICIPATION - Hasibuan, Masnilam (TRIKONOMIKA, 2025)
The government has made significant efforts to increase employment opportunities in a variety of sectors, but these initiatives are not effective in handling the annual increase in workers brought on by a quick increase in population. The study aimed to find out factors that are more dominant and affect the participation of women's workforce in entrepreneurship. The study was quantitative. One hundred were applied women's labor in Padangsidempuan. Data were collected by questionnaires and analyzed by KMO and Bartlett Rotated Component Matrix. The results show that 10 internal sub-factors are grouped into 3 factors given the name of personal desire, circumstances, and help the family economy factors with the most dominant factor being the personal desire factor, with a variance value of 23.366%. External factors are grouped into 3 factors, namely environment, opportunities, and entrepreneurial potential factors, the most dominant factors are environmental factors, with a variance value of 24.727%.